Clinical and instrumental characteristics of axial psoriatic arthritis in combination with hyperuricemia - Yu. L. Korsakova; L. D. Vorobyeva; E. E. Gubar; E. Yu. Loginova; P. O. Tremaskina; T. V. Korotaeva; A. E. Dimitreva; M. M. Urumova (Современная ревматология, 2024)
Objective: to investigate the clinical and instrumental manifestations of axial psoriatic arthritis (axPsA) in combination with hyperuricemia (HU). Material and methods. The study included 71 patients with psoriatic arthritis (PsA): 59 (83%) men and 12 (17%) women. These patients had clinical and imaging evidence of inflammatory changes in the spine and were diagnosed with axPsA. The mean age of patients was 45.7±11.3 years, duration of psoriasis (Ps) was 209.3±163.4 months, and duration of PsA was 51.9±45.5 months. Patients underwent standard clinical, laboratory and radiological examinations. Patients completed the PsAID-12, FACIT-F and FiRST questionnaires and their LEI, MASES, DAPSA, BASDAI, BASFI, BASMI, ASDAS-CRP and BSA indices were assessed. Data on concomitant diseases and drug therapy were also collected. HU was diagnosed at uric acid (UA) level of >360 μmol/L. Patients were divided into two groups – with HU (group 1, n=24, 33.8%) and without HU (group 2, n=47, 66.2%). Results and discussion. The mean UA level was 329.96±80.2 μmol/l. The age of the patients, the duration of Ps and PsA were comparable in both groups. The activity of PsA and spondylitis in the two groups also did not differ. No significant differences were found between the groups in frequency of sacroiliitis or presence of erosions. In the 1st group, the total number of syndesmophytes in two sections of the spine was significantly higher (n=26, 108%) than in the 2nd group (n=39, 83%), p=0.04. In the group of patients with HU, there was a higher intensity of nocturnal spinal pain compared to the group without HU (5.0±2.7 and 3.6±2.8, respectively; p=0.04), more pronounced sleep disturbances (11±5.2 and 7±5.9; p=0.04), higher triglyceride levels (median 0.92 [0; 1.66] and 0.3 [0; 0.6]; p=0.03) and a higher frequency of hypertriglyceridemia (n=2, 8.3% and n=0; p=0.04) and liver steatosis (n=7, 29.1% and n=5, 10.6%; p=0.04, respectively). Patients with HU received antihypertensive therapy (n=10, 41.7% and n=14, 29.8% respectively; p=0.04) and urate-lowering medications (n=4, 16.6% and n=1, 2.1% respectively; p=0.02) significantly more often than patients without HU. Conclusion. HU was present in one third of patients with axPsA. They were more likely to have multiple syndesmophytes in the spine, metabolic disturbances, more severe nocturnal spinal pain and more pronounced sleep disturbances.